PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2017) - Hilda Maulida; Dul Mu'id (Diponegoro Journal of Accounting, 2019)
The purpose of this study was to examine the effect of corporate governance characteristics and audit quality on earnings management. These characteristics are size of audit committe, financial expertise of audit committe, audit commiitte activities, size board of directors, independent board of directors and managerials ownership. The audit quality is proxied as: auditor reputation (Auditor Big Four and Auditor non Big Four) and auditor in industry specialization, while the earnings management is proxied by discretionary accruals.The population in this study were 298 manufacturing companies’ annual report listed on the Indonesia Stock Exchange in 2016-2017. Research data was obtained from the annual report of manufacturing companies in 2016-2017. Based on the purposive sampling method, the samples obtained were 140 companies. The hypothesis in this study was tested using multiple regression analysis.The results of the analysis show that the variable size of audit committee, financial expertise of audit committee, independent board of directors, auditor reputation and auditor in industry specialization affect negative significantly on earnings management. Audit committee activities, size board of directrs and managerials ownership have no affect on earnings management.